Termografia por infravermelho para avaliação de laringe: narrativa e revisão integrativa - Nomura, Emerson Yoshinobu (2017)
This is a narrative and integrative review of infrared thermography for evaluation of the larynx. Since it is a patient with a delayed vocal fold coverage disease is associated with a higher incidence of departures from a part of the economically active population, screening for dysphonic patients is important in reducing morbidity. Thus, an infrared thermography should have a good screening method for evaluation of the larynx. It was therefore intended to perform a review on the production of a solution and be published at the time in the student's larynx and infrared thermography. The search was performed using the terms "thermography and larynx" in the following databases: COCHRANE, LILACS, BIREME, PUBMED, WEB OF SCIENCE, SCOPUS and GOOGLE SCHOLAR. Were included any studies published in any year, without restriction on language, in all sexes, in any age group, larynx of humans or animals or partial parts. At the end of the selection, 2 studies were found that respond to a proposal of objectives. Considering the analyzed publications, there are gaps in the scientific production up to the present moment, and it is necessary to intensify the studies in relation to infrared and larynx thermography in order to be of more effective diffusion for a reduction of the morbidity that causes dysphonia in the population economically active.